Outstanding Early Years Provision in Practice - Book 2. - Scade, Nicola (Andrews UK Ltd. : Andrews UK, 2019)
This book aims to support EYFS practitioners and other childcare professionals to achieve outstanding, creative provision using teaching ideas that are simple and easy to replicate. It contains detailed photographs of investigation activities, small world scenes, fine motor activities and much more, each accompanied by short captions explaining how achievable it is to take the provision to the next level by utilising everyday resources and getting inside the mind of a child!This book also features key questions for practitioners to ask themselves when setting up each activity, enabling them to.